The relationship between psychological capital and organizational silence: A research on telecommunications sector - Dağtekin, Gökhan (My University, 2017)
Bu çalışma, çalışanların örgüt içinde sergiledikleri sessiz kalma davranışlarınınbireysel olarak sahip oldukları psikolojik sermayelerinden etkilenip etkilenmediğininaraştırılması için gerçekleştirilmiştir. Farklı demografik özelliklere sahip 200 telekomsektörü çalışanı üzerinde yüzyüze görüşme ile dağıtılan anketler yoluyla katılımcı verileritoplanmıştır.

The purpose of this study was to investigate whether there is a relationshipbetween psychological capital along with its subdimensions and the reasons fororganizational silence behavior of employees. The research sample was chosen from thetelecommunications sector employees in Istanbul. The questionnaires were delivered viaface to face meeting to 200 participants from a various range of age, educational status,title, and departments.
Keywords: hope; İşletme; iyimserlik; optimism; organizational silence; Örgütsel davranış; örgütsel sessizlik; Öz-yeterlilik; psikolojik dayanıklılık; psikolojiksermaye; psychological capital; resilience; telecommunications sector; telekomünikasyon sektörü Self-efficacy; umut; Yönetim